The Effect of Regional Language Proficiency on The Indonesian Language Skills of Class C Geography Education Students of The 2024 Cohort - Eliana Renintan Br Simatupang; Muhammad Rizky; Randy Marcel Hutauruk; M. Surip (Faculty of Tarbiyah nad Teacher Training, 2026)
Indonesia is a highly multilingual country with over 700 regional languages coexisting alongside Indonesian as the national language. This study aimed to examine the influence of regional language mastery on Indonesian language proficiency among university students. A quantitative approach with an explanatory design was employed. The sample consisted of 16 students from Class C of the 2024 cohort in Geography Education at Universitas Negeri Medan, selected through purposive sampling. Data were collected using questionnaires measuring regional language mastery (8 items) and Indonesian language proficiency (10 items) on a 1–5 Likert scale. Data analysis included descriptive statistics, normality test (Shapiro-Wilk), linearity test, simple linear regression, t-test, and coefficient of determination (R²). The results showed that the average level of regional language mastery was low (mean = 24.3/40), and Indonesian language proficiency was also low (mean = 29.9/50). The hypothesis test revealed no significant influence of regional language mastery on Indonesian language proficiency (t-count = 0.487 < t-table = 2.145; Sig. = 0.634 > 0.05). The coefficient of determination (R² = 0.017) indicated that regional language mastery contributed only 1.7% to Indonesian language proficiency, while 98.3% was influenced by other factors such as learning motivation, reading habits, campus environment, media exposure, and previous educational quality. This study concludes that regional language mastery is not a primary determinant of Indonesian language proficiency among these students.